A novel fixed-time prescribed performance sliding mode control for uncertain wheeled mobile robots - Nguyen, Van-Cuong; Kim, Seong Han (Scientific reports, 2025)
This paper proposes a novel fixed-time prescribed performance sliding mode control method, specifically designed to address trajectory tracking issues in wheeled mobile robots (WMRs) affected by wheel slipping, skidding (WSS), and external disturbances. A new prescribed performance sliding surface is first introduced based on a prescribed performance function (PPF) and a non-singular fast terminal sliding function (NFTSF). This design ensures that tracking errors converge to zero within a fixed time while maintaining stability by keeping error states within predefined limits. A novel fixed-time prescribed performance non-singular fast terminal sliding mode control (FPP-NFTSMC) algorithm is proposed based on the sliding function. The control method integrates a uniform second-order sliding mode (USOSM) algorithm to provide a continuous control signal, effectively reducing the chattering effect. This method combines the benefits of PPF, NFTSMC, and USOSM algorithm to achieve high-precision position tracking, minimize chattering, guarantee fixed-time convergence, ensure tracking errors remain within bounds, and maintain robustness against WSS, and external disturbances. The fixed-time stability of the WMR systems is demonstrated by the Lyapunov stability theory. The effectiveness of the proposed method is validated through simulations of tracking straight-line and U-shaped trajectories.